Music listening preference and the psychological well-being among urban youth in Klang Valley, Malaysia / Danial Kordy - Danial , Kordy (2021)
The main purpose of this is to investigate the youths’ psychological well-being went expose to their music listening preference. The participants are six urban youths ages between 18 to 29 years old living within Klang Valley, Malaysia. The participants are categorized into two different groups, three musicians and three non-musicians. Data was collected through qualitative method semi-structure interview. Due to current global pandemic Covid-19, all the interviews were conducted using Zoom video call during MCO and PKP. The study contributes to the understanding of the relationship of music and urban youth. The findings suggest that the influencing factors of the music listening preference for urban youths are musical background, personality, and musical taste. Furthermore, the reason behind why the urban youths listen to their preference music is entertainment and emotion. Besides, the findings show that the benefits of music listening preference on the well-being of the urban youth are emotional impact and self-reflection. Future studies are recommended to explore various emotions that youths are feeling when they listen to music. From the methodological perspective, future studies are recommended to employ mixed method research with survey and questionnaire with a larger population.